2016
DOI: 10.1016/j.chom.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Action of a Secreted Peptide Required for Fungal Virulence

Abstract: SUMMARY Quorum sensing (QS) is a bacterial communication mechanism in which secreted signaling molecules impact population function and gene expression. QS-like phenomena have been reported in eukaryotes with largely unknown contributing molecules, functions, and mechanisms. We identify Qsp1, a secreted peptide, as a central signaling molecule that regulates virulence in the fungal pathogen Cryptococcus neoformans. QSP1 is a direct target of three transcription factors required for virulence, and qsp1Δ mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 72 publications
5
112
0
Order By: Relevance
“…Only one protein, CNAG_05312, had both an Nterminal signal peptide and a GPI-anchor indicative of plasma membrane association. These secreted peptides were previously reported to play critical roles in C. neoformans virulence (61)(62)(63)(64)(65). Taken together, these results revealed that C. neoformans melanin granules are indeed intimately associated with proteins that employ both a conventional and non-conventional secretory pathway for regulation, and which may be involved with structural and/or functional properties of the cryptococcal eumelanin.…”
Section: Neoformans Melanin Is Molecularly Associated With Non-polsupporting
confidence: 64%
“…Only one protein, CNAG_05312, had both an Nterminal signal peptide and a GPI-anchor indicative of plasma membrane association. These secreted peptides were previously reported to play critical roles in C. neoformans virulence (61)(62)(63)(64)(65). Taken together, these results revealed that C. neoformans melanin granules are indeed intimately associated with proteins that employ both a conventional and non-conventional secretory pathway for regulation, and which may be involved with structural and/or functional properties of the cryptococcal eumelanin.…”
Section: Neoformans Melanin Is Molecularly Associated With Non-polsupporting
confidence: 64%
“…Bone-marrow derived macrophages (BMDMs) were isolated from C56Bl/6 mice and used for phagocytosis assays as described previously [80]. Briefly, BMDMs were plated in a 96-well plate (10,000/well) and simulated with 100 ng/ml Interferon-γ (Roche) starting 24 hr prior to assay initiation and continuing throughout.…”
Section: Methodsmentioning
confidence: 99%
“…Cryptococcus accumulation within macrophages was assessed as described previously [80]. Briefly, BMDMs were plated in 24 well plates at a concentration of 100,000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Ustilago maydis Rep1 protein is also cleaved by kexin-protease and has a structural role in the fungal cell wall (Wödsten et al, 1996;Teertstra et al, 2006). An 11 amino acid long peptide processed by KEX2 in Cryptococcus neoformans is required for virulence and to activate the sexual program (Homer et al, 2016;Tian et al, 2018). Since MiSSP8-RNAi lines are not impaired in hyphal growth or fungal cell-wall sensitivity, it is unlikely that MiSSP8 or its derived peptides are involved in fungal cell wall structure.…”
Section: Discussionmentioning
confidence: 99%